PEMENUHAN HAK POLITIK BAGI PENYANDANG DISABILITAS DI PROVINSI BALI MELALUI IMPLEMENTASI CRPD - Wulandari, Ayu Devi; Erawan, I Ketut Putra; Noak, Piers Andreas Noak (Jurnal Nawala Politika, 2019)
ABSTRACT   Commission on Elections General as the body organizing the elections that have the authority to carry out ranging from planning to implementation has been duly guarantee in full the political rights of every citizen the country without exception for persons with disabilities in the implementation of the election general. This study aims to describe accessibility of elections for persons with disabilities in the province of Bali, map the perception of the disability in its participation at the time of the election, describing the implementation of CRPD towards the fulfillment of the political rights for persons with disabilities in the province of Bali. This study uses a qualitative approach in explaining the fulfillment of rights Politics for Persons with Disabilities in Bali Province through the Implementation of CRPD. The results of this study have not been maximally fulfilled Political Rights of Persons with Disabilities in the Province of Bali.   Keywords  : Persons with Disabilities , Political Rights , CRPD